Identification of a kinesin-like microtubule-based motor protein in Dictyostelium discoideum. - McCaffrey, G (1989)
Dictyostelium discoideum, a unicellular eukaryote amenable to both biochemical and genetic dissection, provides an attractive system for studying microtubule-based transport. In this work, we have identified microtubule-based motor activities in Dictyostelium cell extracts and have partially purified a protein that induces microtubule translocation along glass surfaces. This protein, which sediments at approximately 9S in sucrose density gradients and is composed of a 105 kd polypeptide, generates anterograde movement along microtubules that is insensitive to 5 mM NEM (N-ethyl-maleimide) but sensitive to 200 microM vanadate, and has similar nucleotide-dependent microtubule binding properties to those of kinesins purified from mammals, sea urchin and Drosophila. This kinesin-like molecule from Dictyostelium, however, is immunologically distinct from bovine and squid neuronal kinesins and supports microtubule movement on glass at four-fold greater velocities (2.0 versus 0.5 microns/sec). Furthermore, AMP-PNP (adenylyl imidodiphosphate), which promotes attachment of previously characterized kinesins to microtubules, decreases the affinity of the Dictyostelium kinesin homolog for microtubules. Thus, an AMP-PNP-induced rigor binding may not be a characteristic of kinesins from lower eukaryotes.